2004
DOI: 10.1017/s0031182004005566
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anthelmintic properties of some plants used as livestock dewormers against Haemonchus contortus infections in sheep

Abstract: Gastrointestinal helminth infections remain a major constraint to livestock production globally. This study evaluated anthelmintic efficacy of 7 plants used as dewormers by farmers and pastoralists in Kenya. Thus 3 commercial anthelmintics and 7 plant preparations were tested in lambs infected with 5000 or 3000 L3 Haemonchus contortus in 4 experiments. In the first experiment, ivermectin, levamisole and albendazole were tested in 46 lambs. Seven plant preparations of Hagenia abyssinica, Olea europaea var. afri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 19 publications
3
58
1
1
Order By: Relevance
“…In contrast, the results from studies conducted in Africa on the effects of various plant sources, including pineapple leaves, on ruminant nematodes were less encouraging (Githiori et al, 2004). Although cysteine proteases (bromelain) present in pineapple plant are considered to have some anthelmintic properties, there is a need to identify the active principle in pineapple leaves unequivocally and to investigate its presence in various germplasm existing in Asia and Africa and in different countries within Asia.…”
Section: Plants Containing Anthelmintic Compoundsmentioning
confidence: 99%
“…In contrast, the results from studies conducted in Africa on the effects of various plant sources, including pineapple leaves, on ruminant nematodes were less encouraging (Githiori et al, 2004). Although cysteine proteases (bromelain) present in pineapple plant are considered to have some anthelmintic properties, there is a need to identify the active principle in pineapple leaves unequivocally and to investigate its presence in various germplasm existing in Asia and Africa and in different countries within Asia.…”
Section: Plants Containing Anthelmintic Compoundsmentioning
confidence: 99%
“…The neem tree (Azadirachta indica) is known for its medicinal properties and has been recommended for use against gastro-intestinal nematodes and related problems in many parts of the world (Biswas et al, 2002;Subapriya and Nagini, 2005). However, when leaves of the neem tree were offered to parasitised sheep, either fresh or dried, no anthelmintic effect was recorded against H. contortus (Githiori et al, 2004;Costa et al, 2006). In contrast, in another study, Chandrawathani et al (2006) reported the effectiveness of neem in reducing worm numbers of the same nematode in the abomasa of small ruminants fed on fresh neem leaves on a daily basis.…”
Section: Studies On the Whole Plant: Strengths And Limitationsmentioning
confidence: 99%
“…For example, traditional healers are not always familiar with the parasite species that are most pathogenic for livestock. In a participatory study in northern Kenya, traditional healers identified plants as being very effective antiparasitics if they expelled tapeworm segments (Githiori et al, 2004). The latter are easy to identify, as they are visible with the naked eye, but not as pathogenic as helminth nematodes, whose both parasitic and non-parasitic stages require specialised knowledge and equipment to be identified.…”
Section: Studies On the Whole Plant: Strengths And Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the early 19th century, extracts from the papaya plant (Carica papaya) and many species of fig (Ficus species) have been used against ascarids, tapeworms, whipworms and hookworms by indigenous people, particularly in tropical countries (Berger and Asenjo, 1940). Recently, there has been a resurgence of interest in using plant extracts as anti-parasitic treatments (Hammond et al 1997 ;Tagboto and Townson, 2001 ;Waller et al 2001 ;Githiori et al 2004 ;Anthony et al 2005). Although there are numerous published reports detailing the efficacy of various plant extracts against parasitic nematodes (e.g.…”
Section: Introductionmentioning
confidence: 99%